The Presentation of the Tatars and the Turks in the Legends Related to Miraculous Images/Icons of Our Lady in the 17-18th Centuries in the Eastern Territories of the Polish-Lithuanian Commonwealth - Barysenka, Volha (Eikón / Imago, 2022)
The paper investigates how Christians of different denominations in the Polish-Lithuanian Commonwealth described the Tatars and the Turks in the legends related to the miraculous image/icons of Virgin Mary. It includes both the use of topoi of Tatars devastating the icons during Tatar incursions in the 13-16 centuries, general vision of the Turks and Tatars by the 17 and 18-centuries’ authors, and presentation of them as military enemies in the setting of wars between the Ottoman Empire and the Polish-Lithuanian Commonwealth as well as reflection of these plots in the visual art. The research is based on the analysis of legends and miracles dating back to the 17-18th century and available visual material. It was shown that Christians of three main denominations –Orthodox, Catholics, Greek Catholics– represented the Turks and the Tatars in a similar way and the representation corresponded to the representation of other military enemies independently of religious believes.